2005
DOI: 10.1002/sce.20056
|View full text |Cite
|
Sign up to set email alerts
|

Students' progression of understanding the matter concept from elementary to high school

Abstract: Using the US national sample from the Third International Mathematics and Science Study (TIMSS) and the Rasch modeling method, this study identified the conceptual progression sequence of various matter concept aspects, and compared students' latent abilities against the sequence. We found that the four matter aspects, i.e. conservation, physical properties and change, chemical properties and change, and structure and composition, are interrelated. Although they differ in overall difficulty with an increased d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 39 publications
6
57
1
4
Order By: Relevance
“…Reanalysing the US TIMSS sample, Liu and Lesniak (2005) investigated students' progression in understanding concepts of the following principal aspects of matter, which can be considered an extension of Andersson's (1990) categories, in order to better represent the extensive research on students' conceptions of matter (Liu & Lesniak, 2005, p. 436): structure and composition, physical properties and change, chemical properties and change and conservation. The authors showed that students' understanding of matter develops from an understanding of physical properties and conservation, to understanding chemical properties, and finally advances to an understanding of the structure and composition of matter.…”
Section: Studies In Science Education 183mentioning
confidence: 99%
See 1 more Smart Citation
“…Reanalysing the US TIMSS sample, Liu and Lesniak (2005) investigated students' progression in understanding concepts of the following principal aspects of matter, which can be considered an extension of Andersson's (1990) categories, in order to better represent the extensive research on students' conceptions of matter (Liu & Lesniak, 2005, p. 436): structure and composition, physical properties and change, chemical properties and change and conservation. The authors showed that students' understanding of matter develops from an understanding of physical properties and conservation, to understanding chemical properties, and finally advances to an understanding of the structure and composition of matter.…”
Section: Studies In Science Education 183mentioning
confidence: 99%
“…And although Andersson's (1990) review was followed by a considerable amount of research (e.g. Ahtee & Varjola, 1998;Bar & Galili, 1994;Benson, Wittrock, & Baur, 1993;Boujaoude, 1991;Gabel, 1993;Nakhleh & Samarapungavan, 1999;Stavy, 1991;Watson & Dillon, 1996), Liu and Lesniak (2005) in their review of the literature conclude that still little is known about how students develop understanding of the four aspects of matter and how to foster students' progression in understanding matter as a core idea (Liu & Lesniak, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…There are also studies focused on the development of students' understanding of these concepts (e.g. Johnson, 1998c;Krnel et al, 1998;Liu & Lesniak, 2005). All these studies to a greater or lesser extent investigate the width, depth, or "correctness" of the students' understanding of abstract scientific concepts concerning matter and its transformations more so than investigate students' ability to use these concepts in an everyday context and/or if this use benefits the students' understanding of the phenomena concerned.…”
Section: Introductionmentioning
confidence: 99%
“…A host of research studies investigating sighted students' conceptions of matter has been published recently (Gomez, Benarocch, & Marin, 2006;Eilam, 2004;Liu & Lesniak, 2005;Nakleh, Samarapungavan, & Saglam, 2005;Pozo & Gomez Crespo, 2005;Singer, Wu, & Tal, 2003;Stains & Talanquer, 2007), but the congenitally blind children and youth have been excluded from these studies. In particular, formal operational or abstract reasoning of the congenitally blind was identified by Warren (1994) as a neglected cognitive research area.…”
Section: Introductionmentioning
confidence: 98%